Foliar Application of Humic Acid on Growth and Biomass Improvement of Bok Choy and Red Leaf Lettuce - Anandakumar, Selvaraj; Ranjith, Sellappan; Senthamilselvi, Dhandapani; Rajadurai, Gothandaraman; Sivakumar, Kaliyannan (Plant Science Today, 2024)
Humic acid (HA) is an organic product that is applied as a foliar spray to stimulate the growth and health of various horticultural and agricultural crops. However, its impact on the growth, yield, and health of exotic vegetable crops such as bok choy (Brassica rapa L.) and red leaf lettuce (Lactuca sativa L.) needs to be further explored. The current study aimed to assess the impact of foliar application of HA on the growth and biomass production of bok choy and red leaf lettuce. Notably, the foliar spray of 2% HA resulted in increased plant height, leaf length and width, leaf area, and overall plant biomass production in both bok choy and red leaf lettuce compared to the control group. However, the foliar spray of HA did not significantly affect the shoot and root length, nor the number of leaves of bok choy compared to a control. Moreover, the application of HA significantly improved the shoot length and the number of leaves of red leaf lettuce compared to the control group. Hence, HA emerges as a promising natural resource for enhancing agricultural production sustainably. It could serve as a superior growth enhancer for both bok choy and red leaf lettuce.